Comparative Genome Analyses of 18 Verticillium dahliae Tomato Isolates Reveals Phylogenetic and Race Specific Signatures - Ingram, Thomas W.; Oh, Yeonyee; Adhikari, Tika B.; Louws, Frank J.; Dean, Ralph A. (Frontiers in Microbiology, 2020)
Host resistance is one of the few strategies available to combat the soil borne pathogenic fungus Verticillium dahliae. Understanding pathogen diversity in populations is key to successfully deploying host resistance. In this study the genomes of 18 V. dahliae isolates of races 1 (n = 2), 2 (n = 4) and 3 (n = 12) from Japan, California, and North Carolina were sequenced and mapped to the reference genome of JR2 (from tomato). The genomes were analyzed for phylogenetic and pathogen specific signatures to classify specific strains or genes for future research. Four highly clonal lineages/groups were discovered, including a lineage unique to North Carolina isolates, which had the rare MAT1-1 mating type. No evidence for recombination between isolates of different mating types was observed, even in isolates of different mating types discovered in the same field. By mapping these 18 isolates genomes to the JR2 reference genome, 193 unique candidate effectors were found using SignalP and EffectorP. Within these effectors, 144 highly conserved effectors, 42 mutable effectors (truncated or present in some isolates but absent in others), and 7 effectors present in highly variable regions of the chromosomes were discovered. Of the 144 core effectors, 21 were highly conserved in V. alfalfa and V. longisporum, 7 of which have no known function. Within the non-core effectors 30 contained large numbers of non-synonymous mutations, while 15 of them contained indels, frameshift mutations, or were present on highly variable regions of the chromosome. Two of these highly variable region effectors (HVREs) were only present in race 2 isolates, but not in race 3 isolates. The race 1 effector Ave1 was also present in a highly variable region. These data may suggest that these highly variable regions are enriched in race determinant genes, consistent with the two-speed genome hypothesis.